Strengthening character education planning based on Pancasila value in the international class program - Maisyaroh Maisyaroh; Sri Untari; Tutut Chusniyah; Maulana Amirul Adha; Dedi Prestiadi; Nova Syafira Ariyanti (International Journal of Evaluation and Research in Education (IJERE), 2023)
Education programs planned and implemented in schools have a great impact on the forming of the student’s character and intelligence. This study aims to describe the planning of management to strengthen character education based on Pancasila values in the international class program at laboratory elementary school (Labschool) Universitas Negeri Malang (UM). Qualitative research with a case study research design is used in this study. The data was obtained through unstructured interviews with principals, teachers, education personnel, school committees, and stakeholder. All information is tested for credibility and validity through triangulation. The results of this study showed that planning activities in character education strengthening programs are divided into aspects of learning and non-learning. The formulation of the school's vision and mission is used as the basis for implementing character education in schools, by adjusting learning characteristics that refer to western education patterns, which are combined with eastern culture as outlined in student character-building activities. The impact of implementing school strategies in strengthening student character is inherent in students’ daily lives, both in the environment where they live and in their school environment, and continues to carry over into adulthood.